2007
DOI: 10.1148/radiol.2422051393
|View full text |Cite
|
Sign up to set email alerts
|

Hyaline Cartilage Thickness in Radiographically Normal Cadaveric Hips: Comparison of Spiral CT Arthrographic and Macroscopic Measurements

Abstract: Purpose:To assess spiral multidetector computed tomographic (CT) arthrography for the depiction of cartilage thickness in hips without cartilage loss, with evaluation of anatomic slices as the reference standard. Materials and Methods:Permission to perform imaging studies in cadaveric specimens of individuals who had willed their bodies to science was obtained from the institutional review board. Two independent observers measured the femoral and acetabular hyaline cartilage thickness of 12 radiographically no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 24 publications
1
38
1
Order By: Relevance
“…(11) The difference in the femoral head diameters of these populations would be even greater if the thickness of the articular cartilage were to be taken into account, given that articular cartilage has been shown to contribute approximately 3 mm to the femoral head diameter. (12) However, we found that the thickness of the cartilage was not taken into account during the measurement of femoral head diameter in most earlier studies. (4)(5)(6) For instance, studies by Noble et al, (4) and Hoaglund and Low (5) assessed dry cadaveric bone without an intact articular surface, while Massin et al (6) mainly assessed the femoral head size radiologically.…”
Section: Discussionmentioning
confidence: 91%
“…(11) The difference in the femoral head diameters of these populations would be even greater if the thickness of the articular cartilage were to be taken into account, given that articular cartilage has been shown to contribute approximately 3 mm to the femoral head diameter. (12) However, we found that the thickness of the cartilage was not taken into account during the measurement of femoral head diameter in most earlier studies. (4)(5)(6) For instance, studies by Noble et al, (4) and Hoaglund and Low (5) assessed dry cadaveric bone without an intact articular surface, while Massin et al (6) mainly assessed the femoral head size radiologically.…”
Section: Discussionmentioning
confidence: 91%
“…Wyler et al ( 46 ) assessed the accuracy of multidetector CT arthrography in the hip joint by comparing physical measurements of cartilage thickness from anatomic slices to measurements acquired from multidetector CT arthrograms. They reported a mean ( 39 ) was 0.85-1.72 mm, with maximum thickness values ranging from 1.43 from 3.14 mm.…”
Section: Musculoskeletal Imaging: Acetabular Cartilage Thickness In Amentioning
confidence: 99%
“…In addition, as the hip is situated deep in the body, loss of signal-to-noise ratio occurs, which is compounded by the lack of an effective surface coil [4]. MDCT allows for high-resolution multiplanar reformatted images to be obtained, which enable excellent assessment of both femoral ( Figure 4) and acetabular cartilage ( Figure 5) [9,18,19]. In our series we have demonstrated good correlation between the imaging and arthroscopic findings.…”
Section: Discussionmentioning
confidence: 67%
“…There are few published data on the utility of this technique in the investigation of intra-articular hip pathology. Several studies have investigated the ability of MDCT arthrography to assess cartilage loss in the hip and have demonstrated that its accuracy is equal to, or can outperform, MR arthrography [18][19][20]. There are limited reports regarding the ability of MDCT arthrography to assess labral pathology [9].…”
mentioning
confidence: 99%